ANALISA SENSITIVITAS KELAYAKAN USAHA PT. JASA MARINA INDAH DENGAN BEROPERASINYA GRAVING DOCK 18.000 DWT - Jatmiko, Sukanto; Mulyatno, Imam Pujo (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2010)
Feasibility analysis project is an important component before a project is carried out, one method to feasibility analysis project is sensitivity analysis. The purpose of this study is to determine the feasibility of building graving dock 18.000 DWT at. PT. Jasa Marina Indah with sensitivity analysis method which will be known sensitivity value of graving dock 18.000 DWT in the form of NPV (Net Present Value), IRR (Internal Rate of Return) and B / C (Benefit Cost Ratio), and also to investigate the higest and lowest feasibility. In this study conducted a sensitivity analysis of graving dock 18 000 DWT which is sensitive to the value achieved capacity of graving dock 18 000 DWT each year, such as if the value of its capacity 100% (fully charged), 15% of the available capacity, 10% of the available capacity, and sensitive to the possibility of late payment of installments to the lend capitalResults showed that the sensitivity of graving dock 18 000 DWT highest if the capacity is filled with 100%, While the value of the sensitivity of graving dock 18 000 DWT in the lowest occur if the capacity of the graving dock filled only 10% of the available capacity